FLOOD CONTROL IN SAIL RIVER, PEKANBARU CITY, RIAU PROVINCE - Nurtaufik Tamam, Abdillah
Pekanbaru City is the capital of Riau Province and the largest city in Riau Province. The Sail River that flows in Pekanbaru City is one of the causes of flood disasters every year and causes losses both in terms of economic and social. The Sail River is a tributary of the Siak River which is influenced by the tides of the Siak River due to its sloping river characteristics. The overflow of the Sail River is caused by the small cross-sectional condition of the Sail River, so it cannot accommodate the flood discharge that occurs and the backwater of the Siak River which is affected by tides at the mouth of the Sail River. Based on the results of the calculation, the flood discharge of the Sail River for the 25-year return period is 149.01 m³/s and the influence of tides from the Siak River as far as ± 1 km upstream of the Sail River. Therefore, efforts are needed in the form of technical solutions for handling flood disasters in the Sail River. In this final project, alternative planning for flood control of the Sail River is carried out including pumping stations, normalization, retention ponds, and embankments. The method used starts with hydrological analysis, then one- and two-dimensional modeling using HEC-RAS 6.3.1 software. This includes simulation of river cross-section, flood height, and existing flood inundation area and simulation of the results of planned flood control structures. The combination of flood control structures is expected to be a solution to the flooding problem in the Sail River.